Hungary’s Integration Experiences in the Last 25 Years - Tamás Szemlér (Сравнительная политика, 2017)
In 1989/1990, major systemic changes have taken place in most countries of Central and Eastern Europe. These changes – as part of the fundamental changes in the world order – have also modifi ed the international relations of most countries in the region: after having been part of the Soviet block for more than four decades, they turned towards the West, and tied themselves to different elements – integrations and organisations – of the Euro-Atlantic structure. In this article, we observe this process through the case of Hungary, presenting an overview of the country’s historical and present international relations and objectives. The analysis leads us to the conclusion that the complexity of the relations justifi es a transregionalist approach..